Persepsi atlet terhadap peran ahli gizi olahraga pada pembinaan olahraga prestasi - Anggita, Gustiana Mega; Ali, Mohammad Arif; Kurniawati, Dewi Marfu'ah; Mukarromah, Siti Baitul; Sugiarto, Sugiarto (Jurnal Sporta Saintika, 2023)
Sports coaching is inseparable from the role of sports personnel or supporting experts according to their competence. Fulfilling appropriate and balanced nutrition is one of the main keys to supporting athlete performance. The involvement of sports nutritionists in sports coaching, especially sports achievements, needs special attention. To determine the athlete's perception of the role of a sports nutritionist in sports achievement development. This study is a descriptive survey method. As many as 20 female softball athletes from Central Java were involved in this study using total sampling to determine the sample. Data collection techniques use online questionnaires by utilizing the Google form. Data analysis techniques using descriptive data analysis using percentage correction. The athlete's perception of the role of a sports nutritionist in terms of 1) the authority of a sports nutritionist in the very agree category was 71.58%, 2) the responsibility in the very appropriate category was 80%, 3) the main task in the very suitable category was 71.58 %, 4) job coverage in the very suitable category 74.74%. The role of sports nutritionists in fostering sports achievements based